Dalihan Na Tolu as a Marketing Communication Strategy for PT Sipirok Nauli - Indra Muda; Walid Musthafa S; Beby Masitho Batubara (UMSU, 2023)
The business competition among bus operators is becoming more dynamic, therefore every bus company needs to prepare marketing strategies to attract customers and survive in the competition. This research employs a qualitative descriptive approach with in-depth interviews. The research participants include the Head of the Medan Representative Office, ticket officers, agents, warehouse staff, and 8 loyal customers. Based on the findings, the promotional strategy implemented by the Medan Representative Office focuses more on advertising promotion. This strategy is carried out by publicizing all types of routes and fleets used through the company's Facebook and YouTube accounts. Additionally, the company often distributes calendars to customers towards the end of the year. On the other hand, direct marketing promotion is done through the dalihan na tolu approach, which means ticket officers often use local greetings such as ipar, lae, oppung, bapak uda, amangboru, and anggi to address customers, with the aim of creating familiarity, building a sense of family, and establishing emotional connections through local approaches.